A novel FOXP3 mutation in a Chinese child with IPEX‐associated membranous nephropathy. Issue 6 (18th April 2022) - Tan, Liwen; An, Yunfei; Yang, Qin; Yang, Haiping; Zhang, Gaofu; Li, Qiu; Wang, Mo
Abstract: Background: Immune dysregulation, polyendocrinopathy, enteropathy, X‐linked (IPEX) syndrome is a monogenic immunodeficiency disease caused by forkhead box protein3 ( FOXP3 ) mutation. The kidney is commonly involved in IPEX syndrome, but there were few studies focusing on renal involvement. Methods: Whole‐exome sequencing was used to identify the novel FOXP3 mutation. We collected clinical manifestations, kidney pathology, and gene function of the proband. All the previously published studies with IPEX‐associated renal involvement were reviewed. Results: We report a late‐onset Chinese child with IPEX‐associated membranous nephropathy (MN). Type 1 diabetes mellitus and nephrotic‐range proteinuria are the main clinical manifestations. Whole‐exome sequencing shows a novel c.766A > G mutation in the FOXP3 gene. The literature review indicates that renal manifestations include proteinuria, microscopic hematuria, and renal insufficiency. MN is the most common pathological type in children with IPEX, followed by tubulointerstitial nephritis, interstitial nephritis, minimal change nephrotic syndrome, and membranoproliferative glomerulonephritis. Conclusion: In summary, we report a novel FOXP3 mutation (c.766A > G) with MN stage II in IPEX. In a literature review, MN is the most common pathological type in children with IPEX and proteinuria is the most prevalent clinical feature. IPEX should be considered in the differential diagnosis of MN patients with related endocrine diseases and immune disorders. Abstract : Immune dysregulation, polyendocrinopathy, enteropathy, X‐linked(IPEX) syndrome is a monogenic immunodeficiency disease caused by forkhead box protein3(FOXP3) mutation.We report a novel FOXP3 mutation(c.766A>G) with MN stage II in IPEX. In literature review, MN is the most common pathological type in children with IPEX and proteinuria is the most prevalent clinical feature. IPEX should be considered in the differential diagnosis of MN patients with related endocrine diseases and immune disorders.